Disability in Jewish law - Marx, Tzvi (Jewish law in context, 2003)
In recent decades, record numbers of Jews are taking a newfound interest in their legal heritage - the Bible and the Talmud, the law codes and the rabbinical responsa literature. In the course of this encounter, they may be interested in how these sources relate to the issue of disability, and the degree to which halakhic attitudes to disability are in harmony with contemporary sensibilities. For example, can the blind or those in wheelchairs serve as prayer leaders? Need the mentally incompetent observe any ritual law? Is institutionalization in a special-education facility where Jewish dietary laws are not observed permitted if it will enhance a child's functioning? And how are we to interpret teachings that seem inconsonant with current sensibilities? Disability in Jewish Law answers the pressing need for insight into the position of Jewish law with respect to the rights and status of those with physical and mental impairments, and the corresponding duties of the non-disabled.